C-Arm CT – An Adjunct to DSA for Endoleak Classification in Patients with Endovascular Repair of Abdominal Aortic Aneurysms - Wacker, F. K.; Valdeig, S.; Raatschen, H. J.; Meyer, B. C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To assess the benefit of C-arm CT for classification and procedural guidance during interventional therapy of endoleaks (EL) after endovascular repair (EVAR) of abdominal aortic aneurysms (AAA).Materials and Methods: 12 patients with EL diagnosed with CT but undetermined EL classification (ELC) underwent DSA and transarterial contrast-enhanced C-arm CT. ELC (based on DSA, C-arm CT and CT) assessed during the angiographic procedure served as the standard of reference (SOR). Subsequently, ELC was assessed by a blinded second reader based on DSA or C-arm CT and compared to the SOR. In the case of an interventional procedure (n = 6), the added value of C-arm CT for procedure guidance was assessed retrospectively (1: essential, 2: helpful, 3: additional information without impact, 4: no additional information).Results: The blinded reader classified 9/12 EL using DSA alone and 11/12 EL using C-arm CT alone. In one patient, the temporal resolution provided by DSA was essential to establish the diagnosis. In 6 patients, a type 2 EL without need for therapy was diagnosed. The remaining 6 patients showed EL that were treated immediately (type 1 EL, n = 4: 3 stent graft extensions and one angioplasty; type 2 EL, n = 1: translumbar embolization; type 3 EL, n = 1: sealing of a fabric tear). The information provided by C-arm CT was assessed to be essential in three patients and helpful in two.Conclusion: C-arm CT is an ideal adjunct to DSA. In our pilot study, it helped to localize and classify endoleaks more reliably than DSA alone.Citation Format:• Wacker FK, Valdeig S, Raatschen HJ et al. C-Arm CT – An Adjunct to DSA for Endoleak Classification in Patients with Endovascular Repair of Abdominal Aortic Aneurysms. Fortschr Röntgenstr 2014; 186: 247 – 252
Keywords: aorta; angiography; interventional procedures; aneurysm